Microsoft Windows XP : - Wempen, Faithe (SYBEX, 2005)
This second edition of our visual introduction to Windows XP is completely updated for the latest release, "Reloaded". Much more than an XP user's manual, this highly illustrated guide is packed with easy-to-follow lessons that make learning simple. Just follow the screens and you'll become familiar with the most essential, frequently used tasks. For those who want to explore beyond the basics, you'll find intermediate-level customizing tips for setting up home networking and more.